2008
DOI: 10.1080/00015458.2008.11680213
|View full text |Cite
|
Sign up to set email alerts
|

Acute Claudication caused by Angio-Seal Closure Devices: a Report of Four Cases

Abstract: Femoral artery closure devices are increasingly used after percutaneous arterial interventions to obtain hemostasis at the puncture site. Their efficacy and advantages in patient comfort are established. Nevertheless they can cause their own specific complications. In a five month's period we had to treat four patients with sudden onset invalidating claudication after the use of an Angio-Seal closure device. Malpositioning of the device led to the ischemic complications. We describe and illustrate the pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A recent cost effectiveness study by Resnic et al using a decision analytical model, showed that the routine use of Angio-Seal device post PCI in their institution was associated with 44$ net cost savings per person [7,8]. However it is worth noting that any evaluation of the merits of vascular closure devices should also take into account a trend in the gradual reduction of vascular complications post angiography that has been noted over the last few years [9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cost effectiveness study by Resnic et al using a decision analytical model, showed that the routine use of Angio-Seal device post PCI in their institution was associated with 44$ net cost savings per person [7,8]. However it is worth noting that any evaluation of the merits of vascular closure devices should also take into account a trend in the gradual reduction of vascular complications post angiography that has been noted over the last few years [9].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,5,6] Though recent meta-analyses have failed to demonstrate the clear superiority of VCDs to MC, their use in clinical practice is widely accepted, despite an increase in device-related complications. [4,5,7] MC requires an educated medical staff, manpower, prolonged bed rest, and long-time pressure on the puncture area.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,7] MC requires an educated medical staff, manpower, prolonged bed rest, and long-time pressure on the puncture area. [1][2][3]7] To overcome these disadvantages of compression, an alternative was found: closure devices. VCDs offer many advantages, such as immediate hemostasis, successful use in patients who are highly anticoagulated, and early ambulation and hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations